Detection of Volatile Organic Compounds by Antennal Lamellae of a Scarab Beetle - Li, Ya-Ya; Liu, Deguang; Wen, Ping; Chen, Li (Frontiers in Ecology and Evolution, 2021)
Chemoreceptive sensilla are abundantly distributed on antennal lamellae of scarab beetles. Olfactory reception by these sensory lamellae plays a major role in feeding behaviors and sexual communication of these beetles. A new electroantennogram (EAG) recording technique is here described for evaluation of electrophysiological responses of antennal lamellae of Pseudosymmachia flavescens to sex pheromones and host plant-related compounds. EAG responses were recorded simultaneously from each lamella and the closed antennal club. All test stimuli elicited similar EAG depolarization profiles in all the three lamellae and the closed club although EAG amplitudes from the same lamella or the club varied widely among different chemical stimuli. The mid lamella tended to produce significantly greater EAG responses. EAG responses evoked by a sex pheromone component, anisole, showed a significant correlation with the density of sensilla placodea subtype 1 (SP1). However, no general patterns were obtained for correlations between the density of any test sensilla type and EAG amplitudes evoked by all the six plant volatiles. Single sensillum recordings are needed to elucidate the specific roles of these sensilla in intraspecific sexual communication and perception of host plant volatiles.